Recent development in electrocatalysts for hydrogen production through water electrolysis. (13th September 2021) - Anwar, Shams; Khan, Faisal; Zhang, Yahui; Djire, Abdoulaye
Abstract: Hydrogen is a carbon-free alternative energy source for use in future energy frameworks with the advantages of environment-friendliness and high energy density. Among the numerous hydrogen production techniques, sustainable and high purity of hydrogen can be achieved by water electrolysis. Therefore, developing electrocatalysts for water electrolysis is an emerging field with great importance to the scientific community. On one hand, precious metals are typically used to study the two-half cell reactions, i.e., hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). However, precious metals (i.e., Pt, Au, Ru, Ag, etc.) as electrocatalysts are expensive and with low availability, which inhibits their practical application. Non-precious metal-based electrocatalysts on the other hand are abundant with low-cost and eco-friendliness and exhibit high electrical conductivity and electrocatalytic performance equivalent to those for noble metals. Thus, these electrocatalysts can replace precious materials in the water electrolysis process. However, considerable research effort must be devoted to the development of these cost-effective and efficient non-precious electrocatalysts. In this review article, we provide key fundamental knowledge of water electrolysis, progress, and challenges of the development of most-studied electrocatalysts in the most desirable electrolytic solutions: alkaline water electrolysis (AWE), solid-oxide electrolysis (SOE), and proton exchange membrane electrolysis (PEME). Lastly, we discuss remaining grand challenges, prospect, and future work with key recommendations that must be done prior to the full commercialization of water electrolysis systems. Highlights: Presents key fundamental knowledge of water electrolysis. Progress and challenges of the development of electrocatalysts in the most desirable water electrolytic process. Discussion on grand challenges, prospect, and key recommendations to the commercialization of water electrolysis systems.